Menggali Dampak Penggunaan Aplikasi Kamus Arab-Indonesia di Kalangan Penutur Bahasa Arab - Satyaningrum , Retnowati; Amalia, Jessica Noer; Muqoddam, M. Aziz; Hasaniyah, Nur (Institut Agama Islam Negeri Metro, 2024)
Advances in technology have a significant impact in various fields of life, one of which is in the field of dictionaries. Dictionaries today are not only in printed form but also many have been developed into digital form. In this study, researchers want to provide a better understanding of how technology affects language learning and use. The purpose of this study: 1) to find out what are the advantages and disadvantages of the Arabic-Indonesia dictionary application, 2) to find out the impact of the Arabic-Indonesia dictionary application in the learning process among Arabic speakers. The type of research used in this research is descriptive qualitative. The data collection techniques used are observation, interview, and documentation. The analysis technique used is a case study. The research instrument used was a questionnaire. The population and sample in this study amounted to 11 people. Primary data sources are interviews in the form of questionnaires, and secondary data are journals, articles, books, and proceedings related to this research. The results of this study are the form of learning achievements with the Arabic-Indonesia dictionary application, as well as accessibility in searching for vocabulary meaning can be accessed anytime and anywhere using the Arabic-Indonesia dictionary application via mobile devices or computers, so that Arabic learning can run more efficiently.